Effect of PMRI’s Approach on Students’ Problem-Solving Ability in Geometry Topics - Zohra, Milda; Lubis, Mara Samin (MaPan : Jurnal Matematika dan Pembelajaran, 2025)
Problem-solving skills are abilities that students must master by prioritizing the steps involved in the problem-solving process. However, there are still many Junior High School (SMP) students in grade VII who have difficulties in solving mathematical problems, especially on the topic of geometry. This study aims to determine whether the PMRI approach has an impact on students' problem-solving abilities in geometry materials. The population of this study is all grade VII students, with a total of 134 students. The sample selection was conducted using Simple Random Sampling in grades VII-3 and VII-4 of SMP Negeri 1 Sipirok. The research method used was Quasi quasi-experimental design using a data collection technique through a test (pretest-posttest) consisting of 3 geometry topic essay questions. The data analysis techniques used were descriptive analysis and inferential analysis. Inferential analysis used a hypothesis test or the Independent Samples t-test. After conducting the research, it was found that the average score of students in the control class increased by 18,375 while the experimental class increased by 38,875, meaning that the problem-solving ability of students in the experimental class with the PMRI approach was 11.06 times higher than the control class. T-test results using IBM SPSS Statistics 30, a = 5% or 0.05, showed values sig < a, that is 0.000 < 0.005 which means that there is an influence of PMRI's approach on students' problem-solving abilities in geometry topics. Abstrak: Kemampuan pemecahan masalah merupakan kemampuan yang harus dikuasai siswa dengan mengedepankan langkah-langkah pemecahan masalah. Akan tetapi masih banyak Siswa Menengah Pertama (SMP) kelas VII yang mengalami kesulitan dalam memecahkan masalah matematika, khususnya pada topik geometri. Penelitian ini bertujuan untuk mengetahui apakah pendekatan PMRI berpengaruh terhadap kemampuan pemecahan masalah siswa pada materi geometri. Populasi penelitian ini adalah seluruh siswa kelas VII dengan total 134 siswa. Pemilihan sampel menggunakan simple random sampling yaitu di kelas VII-3 dan VII-4 SMP Negeri 1 Sipirok. Metode penelitian yang digunakan adalah quasi experimental design dengan menggunakan teknik pengumpulan data melalui tes (pretest-posttest) yang terdiri dari 3 soal essai topik geometri. Teknik analisis data yang digunakan adalah analisis deskriptif dan analisis inferensial. Analisis inferensial menggunakan uji hipotesis atau uji-t independent samples test. Setelah dilakukan penelitian, didapat nilai rata-rata siswa kelas kontrol meningkat sebesar 18.375 sedangkan kelas eksperimen meningkat sebesar 38.875, artinya kemampuan pemecahan masalah siswa kelas eksperimen dengan pendekatan PMRI lebih tinggi 11.06 dibandingkan dengan kelas kontrol. Hasil uji-t dengan mengunakan IBM SPSS Statistics 30, a = 5%, atau 0.05 menunjukkan nilai sig < a, yaitu 0.000 < 0.005 yang artinya terdapat pengaruh pendekatan PMRI terhadap kemampuan pemecahan masalah siswa pada materi geometri.